Comparison of the prognostic effect of sarcopenia on atezolizumab plus bevacizumab and lenvatinib therapy in hepatocellular carcinoma patients. Issue 7 (8th June 2022) - Toshida, Katsuya; Itoh, Shinji; Tomiyama, Takahiro; Morinaga, Akinari; Kosai, Yukiko; Tomino, Takahiro; Kurihara, Takeshi; Nagao, Yoshihiro; Morita, Kazutoyo; Harada, Noboru; Yoshizumi, Tomoharu
Abstract: Background and Aim: Sarcopenia has received much attention as a poor prognostic factor in various fields, and has also been reported to worsen prognosis in patients with hepatocellular carcinoma (HCC) treated with sorafenib or lenvatinib (LEN). Atezolizumab/bevacizumab (ATZ/BEV) is recommended as first‐line drug therapy for unresectable‐HCC, but the effect of sarcopenia on patients treated with ATZ/BEV is unknown. Methods: We enrolled 98 patients treated with ATZ/BEV or LEN. Computed tomography performed before the initiation of drug therapy was used to diagnose sarcopenia in accordance with the criteria proposed by the Japanese Society of Hepatology. Patients were divided into two groups based on the presence or absence of sarcopenia in each regimen, and patient characteristics, adverse events, and prognosis were compared. Results: In ATZ/BEV therapy, 57.1% of patients had sarcopenia. The sarcopenia group had significantly more women ( P = 0.0125) and more macroscopic vascular invasion ( P = 0.0270). Sarcopenia had no significant effect on progression‐free survival (PFS) and overall survival (OS). In LEN therapy, 63.4% of patients had sarcopenia. The sarcopenia group was significantly older ( P = 0.0064) and had a higher number of women ( P = 0.0003), a higher neutrophil–lymphocyte ratio ( P = 0.0222), worse albumin–bilirubin grade ( P = 0.0087), and worse best response ( P = 0.0255). PFS ( P = 0.0091) and OS ( P = 0.0006) were worse in the sarcopenia group. In multivariate analysis, age ( P = 0.0362), lymphocyte–monocyte ratio ( P = 0.0365), and sarcopenia ( P = 0.0268) were independent prognostic factors for OS. Conclusion: In ATZ/BEV therapy, sarcopenia does not determine prognosis, and therapeutic efficacy can be expected even in cases of sarcopenia. Abstract : We compared the effect of sarcopenia on the prognosis of unresectable‐hepatocellular carcinoma patients treated with atezolizumab plus bevacizumab and lenvatinib. In patients treated with lenvatinib, sarcopenia was the significant prognostic factor, whereas in patients treated with atezolizumab plus bevacizumab, sarcopenia does not determine prognosis.